Association between the computed tomography findings and operative time for interval appendectomy in children - Takahiro Hosokawa; Yutaka Tanami; Yumiko Sato; Tetsuya Ishimaru; Hiroshi Kawashima; Eiji Oguma (Wolters Kluwer Medknow Publications, 2021)
Purpose: The purpose was to evaluate the association between operative time and findings noted on computed tomography (CT) immediately before interval appendectomy. Materials and Methods: Forty-two children who underwent CT before interval appendectomy were included. We evaluated the association between operative time and these image findings: (1) appendicolith, (2) increased intra-abdominal fat density around the appendix, (3) location of the appendix, (4) ascites, (5) abscess formation and (6) maximum appendix outer wall diameter. Appendix location was classified as (#1) just below the anterior abdominal wall; (#2) retrocaecal or retro-ascending colon and (#3) pelvic. Results were analysed using Pearson's correlation coefficient or Mann-Whitney U test. Results: The mean patient age and operative time were 116.24 ± 38.66 months (range, 31-195) and 67.76 ± 31.23 min (range, 30-179), respectively. Ascites was detected in only one case, and no abscess occurred in any patient; therefore, these findings were not analysed. Factors that significantly prolonged the operative time included increased intra-abdominal fat density around the appendix (absent, 59.43 ± 22.14 [range, 30-108] vs. present, 84.43 ± 40.13 [range, 32-179] min; P = 0.03) and retrocaecal or retro-ascending colon appendix (location 1, 40.83 ± 8.35 [range, 30-50]; location 2, 99.25 ± 18.56 [range, 74-135]; location 3, 64.54 ± 30.22 [range, 30-179] min; P < 0.01). There was a weak but significant association between maximum appendix outer wall diameter and operative time (R = 0.353; P = 0.02). Conclusion: These pre-operative CT findings are important predictors of operative time for interval appendectomy. Radiologists and surgeons should use these specific image findings to predict the operative time and need for additional procedures during an interval appendectomy.